Pengaruh Kemandirian Belajar Terhadap Prestasi Belajar Matematika Siswa Kelas VII SMP Negeri 11 Baubau Di Era Pandemi Covid-19 - Artati Iriana; Putu Yulianingsih (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The Formulation of the problem in this study was whether there was an influence of learning independence on the mathematics learning achievement of VII grade student of SMP Negeri 11 Baubau in the Covid-19 pandemic era. This study aimed to determine the effect of independent learning on mathematics learning achievement of seventh grade student of SMP Negeri 11 Baubau in the Covid-19 pandemic era. This study was an Ex-post facto research. The population in this study were all seventh grade student of SMP Negeri 11 Baubau which consisted of 3 classes with a total of 91 students. The samples taken were 61 students from the total population. Data collection techniques in this study used a questionnaire and documentation. Data were analysed using simple linear regressions analysis. From the results of descriptive analysis of the data showed that the level of student learning independence in general was still in the medium category with a percentage of 70.49%. Meanwhile, the level of student achievement in mathematics was generally still in the medium category with a percentage of 68.85%. Based on the results of calculations using simple linear regressions equation: Y = 0.957 + 0.621X. The results of the study concluded that it showed that learning independence had an effect on the mathematics learning achievement of VII grade student of SMP Negeri 11 Baubau in the Covid-19 pandemic era.this was indicated by the t-count value of 7.227, which was greater than the t-table value of 2.001, which was significant at 0.000 < 0.05.